Predictive factors for conversion from laparoscopic to open cholecystectomy in patients in a private clinic, 2017 - Contreras Alomía, Emilio (2019)
Objective: The aim of the study was to determine the predictive factors of conversion from laparoscopic surgery(CL) to open surgery in a private clinic: Materials and Methods: the study was retrospective based on the reviewof the clinical records of All patients undergoing CL totaling 255 cases between January 2012 and December2016. Results: Results showed a conversion rate of 11.4%; (OR = 79.384, p = 0.000), sex (OR = 6,246, p = 0.002)and age (OR = 1,038, p = 0.038) were the best predictors of the diagnosis of acute cholecystitis. Conclusions:Although there are other variables that have a significant relationship with the conversion of surgery, the statisticalanalysis shows these three variables as predictors.